Optical Coherence Tomography in Multiple Sclerosis - Graves, Jennifer S. (Seminars in Neurology, 2019)
Optical coherence tomography (OCT) grew out of a convergence of rapid advancements in femtoseconds optics research and fiber optic commercial technology. The basic concept of OCT is to “see” into tissues using light echoes, analogous to the sound echoes of ultrasonography. Multiple A-scans are assembled into a B-scan two-dimensional image of the tissue of interest. Retina is an ideal tissue for evaluation by OCT, since the eye is designed to minimize light scattering through the anterior chamber and vitreous. OCT has had a significant impact on the field of multiple sclerosis, where it has allowed direct imaging of the myelin-free segments of axons and cell bodies of retinal ganglion cells. Together with precise functional measurements of the afferent visual system, the addition of robust structural measurements of retinal injury has allowed for an unprecedented ability to correlate clinical effects with the degree of neuronal loss. In addition, OCT has proven helpful to distinguish different forms of demyelinating disease, such as multiple sclerosis (MS) and neuromyelitis optica, and has provided ideal outcome measures in remyelination and neuroprotection trials.
Keywords: optical coherence tomography; multiple sclerosis; neuromyelitis optica